2000
DOI: 10.1177/026988110001400206
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of amisulpride (50 mg and 200 mg) and haloperidol (2 mg) on cognitive function in healthy elderly volunteers

Abstract: In this double-blind, placebo controlled, four-way cross-over trial in 16 healthy elderly volunteers, the acute effects of haloperidol 2 mg, amisulpride 50 mg and 200 mg, were assessed on a range of tests of cognitive function. On each study day, cognitive performance was assessed prior to dosing and at 2, 4, 6, 9, 12 and 24 h after dosing with the following tests from the Cognitive Drug Research computerized assessment system: simple reaction time, digit vigilance task, choice reaction time, visual tracking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 20 publications
4
34
0
Order By: Relevance
“…However, patients treated with typical or atypical neuroleptics did not differ significantly on clinical or neuropsychological scales. This might also indicate that cognitive impairment as a side effect of neuroleptic therapy [17][18][19][20][21][22][23][24] was not different between atypical and typical antipsychotic drugs in our sample. Of course, it has to be taken into account that the sample size was small.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, patients treated with typical or atypical neuroleptics did not differ significantly on clinical or neuropsychological scales. This might also indicate that cognitive impairment as a side effect of neuroleptic therapy [17][18][19][20][21][22][23][24] was not different between atypical and typical antipsychotic drugs in our sample. Of course, it has to be taken into account that the sample size was small.…”
Section: Discussionmentioning
confidence: 88%
“…Patat et al [23] demonstrated that amisulpride (50 mg once daily for 4 days) is devoid of detrimental effects on EEG, psychomotor and cognitive performance after sleep deprivation. The general absence of cognitive impairments with amisulpride (50 and 200 mg) was shown by Legangneux et al [24], while haloperidol (2 mg) showed a general tendency to impair performance. In summary, typical antipsychotic drugs such as haloperidol seem to impair cognitive and psychomotor function, while atypical drugs such as olanzapine or amisulpride are devoid of such detrimental effects (at least over a short observation period).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, these patients may be more susceptible to drug interactions and metabolic changes (Katona, 2001). It is generally acknowledged that the atypical antipsychotic amisulpride has a satisfactory safety profile (among others good pharmacokinetic and cognitive-sparing profile) (Coulouvrat and Dondey-Nouvel, 1999;Ramaekers et al, 1999;Leucht, 2004), promotes social functioning (Saleem et al, 2002), and therefore seems to be a good candidate for treatment of the elderly patients (Hamon-Vilcot et al, 1998;Legangneux et al, 2000). This drug has been shown to be efficacious in dysthymic (Bellino et al, 1997) and psychotic (Möller et al, 2005) elderly patients and in the treatment of behavioural disturbances of patients with moderate to severe Alzheimer's disease (Mauri et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the elderly (aged 65-80 years) healthy volunteers performed better with single or repeated doses of amisulpride (50-400 mg/day) than with haloperidol (2-4 mg/day) on a range of psychometric and/or cognitive tests [15] . In addition, SPECT imaging showed a significant increase in cerebral blood flow (p !…”
Section: Discussionmentioning
confidence: 83%